Reshaping the Culture: Improving and Integrating Social Capital to Affirm Land Use Control A Case of Bali in Democratic Decentralization Era - Putra, I Wayan Indrabayu Pandi; Pratama, Reba Anindyajati (Department of Urban and Regional Planning, Diponegoro University, 2014)
Abtsract: One of the important issues emergences in the context of spatial planning is about community participation. In Indonesia, this issue widely spread in line with development of decentralization system and low level of trust to government. In Bali, problem in land management became crucial issue in regard with rocket development of tourism sector. Triangle conflicts among Indigenous Village, State Government and investor became a common things today. Social capital as an instrument of control is absolutely necessary to monitor the implementation of spatial planning. In regard with endogenous concept in contemporary urban planning, and considering the weakness and limitations of current land use control tools this paper discus and propose an idea to enforce the uses of social capital to support and affirm land use control. This paper began with elaboration of the challenges and conflict of land management in Bali, followed by analysis weakness and limitations of existing regulations and finally ends up with an idea to enforce the function of social capital through institutional reform. Based on the discussion, integrating social capital can be done through accommodating the value into concept of spatial planning and involving indigenous village as institution control for the implementation of spatial plan.Keywords: indigenous, land conflict, participation, social capital, spatial planning